MANAGEMENT ASPECTS OF INFORMATION COMPLETENESS OF ENTERPRISE’S EXPORT PLAN UNDER CONDITIONS OF FOREIGN MARKET DEVELOPMENT - SAVITSKYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The essence of separate component and elements of export plan of industrial enterprise’s under current conditions of entering the external market and its potential positions strengthening has been researched. The actuality of enterprises’ operating plans adaptation under the points of transformational economic changes caused by military actions in Ukraine has been interpreted. The advantages of in-depth informatization of economic activity organization of national producers under the influence of European Union (EU) rules have been presented. The essence of current export planning under the demands of foreign market entering has been given. In order to highlight the practical questions of managerial process of enterprise’s production by export plan indicators, it was interrelated two core stages of export manufacturing in accordance of main functions of management. In the context of conceptualization and evaluating stage it was listed and interpreted general information that needs to be in export plan and includes characteristics of market, competiveness, enterprise’s values, financial possibilities and costs. In the context of stage of realization there were listed main production units that concerns capacities, volumes and staff, underlined prospective parts that deals with financial, analytical and modeling views of profitability measurement. In accordance of presented stages the justification of structural components of industrial producer’s export plan formation has been proposed. The meaning of informative completeness management of general, cost, production and prospective parts of export plan is underlined. The factors and determinants that determine the profitability of export-oriented enterprise, destabilize the economic balance and can affect the cost items of its production processes have been emphasized. The organization structure of information completeness of industrial enterprise export plan has been proposed and built, where interrelation between administrative staff and main performers has been singled out.